Discriminatory Pricing of Over-the-Counter Derivatives - Hau, Harald; Hoffmann, Peter; Langfield, Sam; Timmer, Yannick (Management Science, 2021)
For the first time, new regulatory data allow precise measurement of price discrimination against nonfinancial clients in the foreign exchange derivatives market. Consistent with the theoretical literature, transaction costs vary systematically with measures of client sophistication. The median client pays 10.9 pips more than blue-chip companies because of its lower level of sophistication, which compares with a sample average effective spread of 6.9 pips. However, price discrimination is fully eliminated when clients trade electronically on multidealer platforms. We also document that less sophisticated clients incur additional costs when trading with their relationship bank and in fast-moving markets, but only for bilaterally negotiated contracts. This paper was accepted by Haoxiang Zhu, finance.